Developing a secured image file management system using modified AES - Heidilyn V. Gamido; Marlon V. Gamido; Ariel M. Sison (Bulletin of Electrical Engineering and Informatics, 2019)
Images are a means to share and convey relevant data in today’s digital world. This paper presents an image file management system to provide a platform for distributing and viewing images in a secured manner. The shared image files are stored in the server in an encrypted manner to provide additional security to the owner of the file. A modified AES algorithm using bit permutation was used to encrypt the image files. Based on the experimental result, image files were successfully encrypted in the server and can only be decrypted by the intended recipient of the file providing an efficient and reliable way of exchanging images.